Elimination of Photovoltaic Mismatching With Improved Submodule Differential Power Processing - Chu, Guanying; Wen, Huiqing; Yang, Yong; Wang, Yiwang (IEEE transactions on industrial electronics (1982), 2020)
Differential power processing (DPP) is a promising architecture to solve the issue caused by mismatches among photovoltaic (PV) submodules. To eliminate the mismatch power losses, this paper presents an optimized PV-to-bus DPP system with submodule-level individual maximum power point tracking (MPPT) and module-level minimum-power tracking (MPT) simultaneous implementation according to the built mathematical model of the power processed by DPP converters with respect to the string current. Furthermore, a flexible time-sharing algorithm is adopted to reduce the number of MPPT units. Compared with other solutions, such as PV optimizer, the proposed scheme can reduce the effects of mismatches to the minimum regardless of mismatch conditions. The system cost is reduced since only one adaptive MPPT controller is required. Besides, the system efficiency is improved due to the true MPPT implementation and MPT control. Both simulation and experimental tests are provided to validate the effectiveness of the proposed scheme.